2014
DOI: 10.1097/ccm.0000000000000411
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Two Different Protocols of Do-Not-Resuscitate Orders in a Medical ICU*

Abstract: Our study showed that some clinical/demographic factors predicted do-not-resuscitate comfort care orders. This study also suggested that Ohio's Do-Not-Resuscitate Law, clearly indicating two different protocols of do-not-resuscitate orders, facilitated early do-not-resuscitate decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
1
9
1
Order By: Relevance
“…Independent patient characteristics associated with a DNR decision were older age and more severe clinical illness. Chen et al 7 conducted a single-center study in Northeast Ohio, also reported that older age, severity of illness at admission to the medical ICU, and race/ethnicity were significantly associated with a DNR order written during ICU stay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Independent patient characteristics associated with a DNR decision were older age and more severe clinical illness. Chen et al 7 conducted a single-center study in Northeast Ohio, also reported that older age, severity of illness at admission to the medical ICU, and race/ethnicity were significantly associated with a DNR order written during ICU stay.…”
Section: Discussionmentioning
confidence: 99%
“…The generalizability of the results of this single-center study is as good as several prior studies as indicated by the percentage of patients who had a DNR order written, age, and severity of illness upon SICU admissions. 7,11,31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies were focused on examining the factors associated with DNR decisions. The prevalence of DNR varied from setting to setting and institution to institution, from approximately 4% to 41% 4 5 6 7 8 . Some studies examined health care professionals’ attitudes toward DNR, and showed that physicians and nurses were reluctant to perform a variety of physiologic monitoring modalities, medical interventions, and nursing care for DNR patients 9 10 11 12 .…”
mentioning
confidence: 99%
“…For example, Hemphill et al ’s and Shepardson et al ’s studies both showed that, for stroke patients, there was an increased risk of death for DNR patients compared with patients without DNR 15 16 ; Kazaure et al reported that, for surgical patients, a DNR order remained an independent risk factor associated with death 17 . In addition, not only the studies conducted in general wards, but also those conducted in intensive care units showed that a DNR decision was significantly associated with an increased risk of death 8 18 .…”
mentioning
confidence: 99%